The Teachers’ Perception Toward the Use of Google Classroom in Online Learning on Junior High School - Chelsea Yohana Panjaitan; Ni Nyoman Padmadewi; Kadek Sintya Dewi (Universitas Pendidikan Ganesha, 2022)
Online learning encourages the used of several online learning platforms in order to do the learning activities. There are several online learning platforms that commonly used in school such as Edmodo, WhatsApp, Google Classroom, Zoom, etc. Google Classroom is one of the online learning platforms that commonly use in school. This platform is an application that provides the creation of classrooms in cyberspace. Google Classroom has many features that can be used as a means for the distribution of tasks, assignments submission as well as assessment. This study aimed to analyses teacher’s perception toward the used of Google Classroom in online learning in junior high school. In collecting the data, this article use mixed method with quantitative and qualitative phases in collecting and analyzing the data. The data were collected from questionnaire and interview. The result of the research showed that the teachers perceived that the implementation of Google Classroom as an online learning media could improve student performance. Moreover, the used of Google Classroom in school was beneficial for both teachers and students in order to do the learning process.